Persepsi Nazhir dalam Pendaftaran Tanah Wakaf - Ratnasari, Variahatul; Ridlwan, Ahmad Ajib (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2019)
Abstract This study aims to determine the relationship between Nazhir's knowledge and attitude in the Krian District of Sidoarjo Regency with their behavior in the registration of waqf land. This research was conducted with an associative descriptive approach where the data obtained from the questionnaire in the form of numbers. The number of samples used in this study amounted to 80 respondents who are managers of land waqf in Krian District, Sidoarjo Regency and use simple random sampling techniques. This study uses a questionnaire with a Likert scale. The results of this study indicate that Nazhir's knowledge and attitude related to the procedure for registering waqf land has a moderate and significant correlation with Nazhir's behavior in carrying out the act of registering waqf land. That is due to the lack of socialization from authorized institutions to the community to manage the administration of waqf land. The knowledge and attitude possessed by Nazhir regarding the registration of waqf land would increase Nazhir's behavior or actions in registering the waqf land. This research was conducted to prevent future disputes caused by the absence of written evidence as waqf land.AbstrakPenelitian ini bertujuan untuk mengetahui hubungan pengetahuan dan sikap Nazhir di Kecamatan Krian Kabupaten Sidoarjo dengan perilaku mereka dalam pendaftaran tanah wakaf. Penelitian ini dilakukan dengan pendekatan deskriptif asosiatif dimana data yang diperoleh dari kuisioner berupa angka. Jumlah sampel yang digunakan pada penelitian ini berjumlah 80 responden yang merupakan pengelola wakaf tanah di Kecamatan Krian Kabupaten Sidoarjo dan menggunakan teknik simple random sampling. Penelitian ini menggunakan kuisioner dengan skala likert. Hasil penelitian ini menunjukkan bahwa pengetahuan dan sikap Nazhir terkait tata cara pendaftaran tanah wakaf memiliki korelasi sedang dan signifikan dengan perilaku Nazhir dalam melakukan tindakan pendaftaran tanah wakaf. Hal itu dikarenakan kurangnya sosialisasi dari lembaga yang berwenang kepada masyarakat untuk mengelola administrasi tanah wakaf. AdanyaÂ  pengetahuan serta sikap yang dimiliki Nazhir terkait pendaftaran tanah wakaf akan meningkatkan perilaku atau tindakan Nazhir dalam mendaftarkan tanah wakaf. Penelitian ini dilakukan untuk mencegah adanya persengketaan yang terjadi dikemudian hari yang disebabkan karena tidak adanya bukti tertulis sebagai tanah wakaf.